Blended MOOC (bMOOC) Learning Model: Language Learning Course Students’ and Teacher’s Self-Reported Experience - Kilci, Yilmaz (2016)
Massive open online learning courses (MOOCs) have played an important role in providing distance learning options to students and have left a long lasting influence on the traditional educational systems and practices. However, a debate has been conducted around whether the utilisation of MOOCs in different ways might address the limitations of stand-alone MOOCs and help capitalising on MOOCs in a more effective way. Blended learning model has been considered as one of these novel ways and the term ‘blended MOOC’or ‘bMOOC’, has been emerged. However, little is known about the different types of bMOOC models and there is need to further investigate these models, particularly complementary model. A qualitative single case-study approach was adopted to understand students’ and teacher’s self-reported experience at individual level within the complementary blended MOOC model apart from higher education level, particularly at language learning course levels in the UK in the light of qualitative research application. The weekly semi-structured interviews with students and one semi-structured interview with the teacher at the end of the research process were conducted. Non-participant observation and the researcher’s personal field notes were also some supplementary research methods through the exploration. The study revealed that this model prepared students for upcoming class and thus deepened their understanding. Although the findings highlighted that the views around these points differentiated with different cultures and previous learning habits, online and face-to-face social interaction and local teacher and peer presence were reported as considerable points. These points were stressed as the strengths of this model to increase the low completion rates of MOOCs. Moreover, while reviewing the materials on MOOC, utility value, community sense and autonomy were important points for students. This study also illustrated the reported benefits and challenges of bMOOC model, implementation process of it and its actors’ reactions and reflections towards it. For future studies, this study highlighted some open issues to investigate further such as using multiple MOOCs in one bMOOC model or using other learning sources iv apart from MOOCs as ingredients of the model. Furthermore, the study underlined that CoI model and its three components, teacher presence, cognitive presence and social presence, might be considered within bMOOC model in the future. The researcher believes that there is still a need to further investigation of complementary and flipped bMOOC models by focusing on some certain points such as professionalised, personalised and situated learning and addressing the diversity of learners within these models.